Digestive Endoscopy: Inside the Evidence and Outside - Anderloni, Andrea; Binda, Cecilia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Over the years, digestive endoscopy has gone through a revolution. With different technological improvements, its diagnostic role is indeed becoming more and more sophisticated and is even moving closer to pathological evaluation. Above all, its therapeutic purpose is to date the first line of treatment for several gastrointestinal diseases. Importantly, the role of digestive endoscopy is also crossing over the mere concept of the GI tract and digestive diseases and will probably find a place in a more holistic concept of health. In this Special Issue, several emerging techniques are addressed, highlighting how endoscopy is emerging as a minimally invasive treatment procedure for several gastrointestinal diseases and post-surgical complications. However, crucial to this is the safety of all endoscopic processes, starting from endoscopic suites to the management of intra- and post-procedural complications.